Insakralitas Pemilihan Jodoh Dalam Pernikahan Keluarga Kontemporer - Anisa Puspa Rani; Dwi Setiawan Chaniago; Syarifuddin Syarifuddin (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2019)
The shifting pattern of marriage is essentially not only in the process or the determination of mere matches. Further impacts on achieving the family's own goals and functions. Nowadays, various forms of disorganization in the family are common. The high problems in the family are not separated from the input of the marriage process that is in the assumption of the researcher due to the insacramalization of marriage. The purpose of this research is to know the cause of marriage insakrality in the election of the soul mate in contemporary families and identify forms of marriage insakrality in the election of the match in contemporary families. The study uses an interactionist sociological perspective focusing on identifying the person's knowledge, experience, wishes and consideration in choosing a soul mate and marriage. The results of the study showed the form of marriage insakality in the selection of the match in contemporary families can be seen from the eligibility indicators seen in the two main dimensions, the capability (capability) of prospective spouse with Consideration of religious aspects, and economic aspects. While the second dimension is allowed or not the selected spouse and marriage are held. The cause of marital insakality in the election of a match in contemporary families distinguished in two forms, the first insakrality caused not to match the chosen mate, both the insakrality caused by the miss-interpretation in the understand the circumstances of sosio-culture.